2012
DOI: 10.1093/heapol/czs105
|View full text |Cite
|
Sign up to set email alerts
|

Community participation of cross-border migrants for primary health care in Thailand

Abstract: This is the first report of the large-scale utilization of migrants as health volunteers in a migrant primary-healthcare program. The program recruited migrants who volunteered to serve their communities. This study explores the identities of these volunteers, their relationship with program management, and their attitudes. The study also investigates the impact of the volunteers, from the migrants' and healthcare workers' perspective. The study was conducted in two provinces, Tak (northern Thailand) and Samut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Participants were predominantly female (70%) with a majority aged 30–49 (62%). Another study from two Thai border provinces similarly found that most (56.9%) of the migrant volunteers were women ( Sirilak et al 2013 ). In our sample, most CHVs spoke Burmese, self-identified as documented migrants (60%), and had been working as a CHV for 2 or more years (54%).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Participants were predominantly female (70%) with a majority aged 30–49 (62%). Another study from two Thai border provinces similarly found that most (56.9%) of the migrant volunteers were women ( Sirilak et al 2013 ). In our sample, most CHVs spoke Burmese, self-identified as documented migrants (60%), and had been working as a CHV for 2 or more years (54%).…”
Section: Resultsmentioning
confidence: 95%
“…The way that CHVs framed their rationale for volunteering may be related to the way they see themselves, as members of a minority group in a foreign country where they need to work together in solidarity. Our survey did not collect information on reasons for volunteering but a CHV survey with a similar migrant population found that 98.1% believed that volunteer work assisted members of their ethnic group ( Sirilak et al 2013 ). This model of care, where migrants are embedded in treatment programmes as medics and volunteers, is not limited to TB programmes but is commonly used by numerous organizations that provide healthcare to migrant populations along the border.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that interpreters encouraged care-seeking and built goodwill with employers. The Migrant Health Volunteer model holds promise, although it has only been implemented in two coastal provinces [65]. In another large-scale NGO program, Migrant Field Officers provide similar support alongside negotiating disputes with police, employers and health workers [66].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies are conducted in LMICs. In Thailand, one study describes the benefits and challenges of implementing a Migrant Health Volunteer (MHV) program in two provinces [19]. In Malaysia, a recent survey with migrant workers found that those who preferred other languages for clinical communication (not English or Malay) were 2.7 times more likely to delay treatment when severely sick, compared to those who preferred to communicate in Malay [20].…”
Section: Introductionmentioning
confidence: 99%